Highly Diversified Pandoraea pulmonicola Population during Chronic Colonization in Cystic Fibrosis - Dupont, Chloé; Aujoulat, Fabien; Chiron, Raphaël; Condom, Pauline; Jumas-Bilak, Estelle; Marchandin, Hélène (Frontiers in Microbiology, 2017)
Several environmental bacteria are considered as opportunistic pathogens in Cystis Fibrosis (CF) and are able to persistently colonize the respiratory tract (CFRT). Beside Pseudomonas aeruginosa and Burkholderia cepacia complex, Pandoraea spp. are defined as pathogenic. During chronic colonization, adaptive evolution and diversified population have been demonstrated, notably for P. aeruginosa. However, the persistence of Pandoraea in the CFRT remains largely unexplored. We studied genomic and phenotypic traits of Pandoraea pulmonicola isolates successively recovered from the airways of a single CF patient and relate the results to qualitative and quantitative evolution of other cultivable pathogens and to patient clinical status. A total of 31 isolates recovered from 18 sputum samples over a 7-year period in a single CF patient were studied. Genome dynamics was assessed by Pulsed-Field Gel Electrophoresis, ERIC-PCR fingerprinting and 16S rRNA gene PCR-Temporal Temperature Gel Electrophoresis. Phenotypic features included antimicrobial susceptibility, motility, biofilm production and virulence in Caenorhaditis elegans model. Variability was observed for all the characteristics studied leading to highly diversified patterns (24 patterns) for the 31 clonally related isolates. Some of these modifications, mainly genomic events were concomitantly observed with CFRT microbiota composition shifts and with severe exacerbations. The diversity of P. pulmonicola population studied, observed for isolates recovered from successive samples but also within a sample suggested that existence of a diversified population may represent part of the patho-adaptive strategy for host persistence in the heterogeneous and fluctuating CFRT environment.